2014
DOI: 10.1111/jcpe.12302
|View full text |Cite
|
Sign up to set email alerts
|

Microbial signature profiles of periodontally healthy and diseased patients

Abstract: Aim: To determine microbial profiles that discriminate periodontal health from different forms of periodontal diseases. Methods: Subgingival biofilm was obtained from patients with periodontal health (27), gingivitis (11), chronic periodontitis (35) and aggressive periodontitis (24), and analysed for the presence of >250 species/phylotypes using HOMIM. Microbial differences among groups were examined by Mann-Whitney U-test. Regression analyses were performed to determine microbial risk indicators of disease. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
158
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 159 publications
(173 citation statements)
references
References 40 publications
12
158
0
3
Order By: Relevance
“…OT930) were significantly more predominant in diseased individuals compared to PH. Many of these microorganisms are associated with caries, periodontal and endodontic infections [6972], but they have also been isolated from extra-oral infections or systemic conditions [5254,7375]. In contrast, S. australis and G. adiacens have been related to periodontal health [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…OT930) were significantly more predominant in diseased individuals compared to PH. Many of these microorganisms are associated with caries, periodontal and endodontic infections [6972], but they have also been isolated from extra-oral infections or systemic conditions [5254,7375]. In contrast, S. australis and G. adiacens have been related to periodontal health [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that there are many qualities of oral biofilm that can lead to the development or suppression of biofilminduced pathogenicity (54)(55)(56). The presence of a few uncultivable species, such as those of the candidate bacterial division TM7, could be highly significant for the manifestation of oral diseases, particularly periodontal disease (57).…”
Section: Discussionmentioning
confidence: 99%
“…In chronic periodontitis, high proportions of the red and orange complexes are observed, while A. actinomycetemcomitans is a major pathogen associated with aggressive forms of periodontitis [83]. However, recent studies have shown that in addition to A. actinomycetemcomitans, aggressive periodontitis may be modulated by a consortia of pathogenic species [85][86][87][88]. Microorganisms associated with other infections in the human body, as well as novel potential pathogenic species, including not-yet-cultivated microorganisms, may also play a role in the initiation, progression, and/or severity of various forms of periodontal diseases [89][90][91][92][93][94][95].…”
Section: Periodontopathogenic Biofilmmentioning
confidence: 98%